Folk-Based Farm Waste with Akar Wangi (Vetiveria zizanioides (L.) Nash) Beautiful to look at and Inhale Fragrance from Garut West Java - Ine shinta dewi; Retno Latifah; Putri Wahyu Prasetyaningrum (Business and Entrepreneurial Review, 2020)
The Fragrant root is a plant that can produce fragrant root oil through the distillation process. Indonesia is one of the largest producers of fragrant root oil in the world, the center of producing fragrant root oil in Indonesia is in Garut Regency. From the results of the study, in addition to producing pure oil, fragrant root waste can also be processed into handicrafts of secondary needs such as bags and souvenirs by weaving